Factors Affecting The Survival Trend In Oesophageal Malignancy- A Hospital Based Study - Sarker, MK; Sarker, MM; Bhuiyan, MFK; Khan, MMR; Raihan, ASMA (TAJ: Journal of Teachers Association, 2018)
Oesophageal cancer is a gastrointestinal malignancy with insidious onset and poor prognosis. The disease predominantly affects the older age groups with pick incidence between 60 to 70 years of age. The total number of oesophageal cancer patients available for the study within the stipulated time was 43. Among them 60.47% patients were male and 39.53% patients were female, 06.98% belonged to age group 31-40, 16.28% belonged to age group 41-50, 37.21% belonged to age group 51-60, 23.25% belonged to age group 61-70 and 16.28% patients were >70 years of age. Mean age was 59.95 years ± 12.63 SD. In our study, 33.3% survived ≤3 months, 09.1% 4–6 months, 15.2 % 7–9 months, 06.1% 10–12 months, 27.2% 13–24 months and 09.1% >24 months. Among the expired patients, 09.10% got curative treatment and rest of 90.90% got palliative treatment. Those who got curative treatment 66.7% survived 13–24 months and 33.3% > 24 months. Those who got palliative treatment 36.7% survived ≤3 months, 10.0% 4–6 months, 06.7% 10–12 months and 30.0% 13–24 months. Overall median survival was 08 months, for curative treatment 18 months and for palliative treatment 07 months. TAJ 2014; 27(1): 38-43